2012
DOI: 10.1186/1471-2458-12-984
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physician’s recommendation on seasonal influenza immunization in children with chronic diseases

Abstract: BackgroundDespite recommendations by Health Authorities, influenza immunization coverage remains low in children with chronic diseases. Different medical providers involved in the management of children with chronic conditions may affect the pattern of influenza vaccine recommendations and coverage. The likelihood of vaccination by type of provider in children with chronic conditions is poorly understood. Therefore, the objectives of this study were to analyze the pattern and the effect of recommendations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 20 publications
2
44
0
2
Order By: Relevance
“…In corroboration with previous studies [19][20][21][22][23][24], the most important determinant of influenza vaccine coverage amongst the children in this study was a recommendation by a healthcare worker. High risk children accessed outpatient pediatric clinics at a tertiary pediatric hospital frequently and also had higher vaccine coverage.…”
Section: Discussionsupporting
confidence: 91%
“…In corroboration with previous studies [19][20][21][22][23][24], the most important determinant of influenza vaccine coverage amongst the children in this study was a recommendation by a healthcare worker. High risk children accessed outpatient pediatric clinics at a tertiary pediatric hospital frequently and also had higher vaccine coverage.…”
Section: Discussionsupporting
confidence: 91%
“…While studies of vaccine acceptability among primary caretakers in the community are limited, willingness to accept influenza vaccine in this study was similar to acceptability observed among healthcare workers in Kenya16 and Cote d'Ivoire17 and higher than acceptability observed among pregnant women in Cote d'Ivoire18 during the 2009 influenza A (H1N1) pandemic. We did not explore how clinician recommendations, which have been shown to influence vaccination attitudes and practices,19 might affect willingness to receive influenza vaccine in this population. Health messaging in South African communities should consider highlighting influenza as a disease distinct from upper respiratory infections and should clarify that influenza can cause severe outcomes that may be mitigated by vaccination and other prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding factors associated with and obstacles preventing Tdap receipt will aid in the development of future interventions to improve Tdap vaccine coverage in this population. It has been well described in the pediatric population that provider recommendation and source of vaccine information play an important role in parental vaccine decision making [6][7][8][9][10][11]. However few studies have described the association between these factors and adult vaccine receipt.…”
Section: Introductionmentioning
confidence: 99%